(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Familial cerebral cavernous malformation (FCCM) is a hereditary vascular disorder characterized by multiple abnormal capillary lesions in the brain that can lead to seizures, hemorrhage, and neurological deficits. While surgical resection remains the primary treatment for symptomatic lesions, its effectiveness in FCCM is limited due to the presence of multiple and often surgically inaccessible lesions. Recent advances in molecular biology have improved understanding of the genetic and signaling mechanisms underlying FCCM, including mutations in the KRIT1 (CCM1), CCM2, and PDCD10 (CCM3) genes and dysregulation of pathways such as RhoA/ROCK, MEKK3–MEK5–ERK5, PI3K/mTOR, and oxidative stress signaling. These discoveries have led to the investigation of several potential pharmacological therapies, including rapamycin, ponatinib, fasudil, statins, propranolol, vitamin D₃, and antioxidants such as tempol. Preclinical and early clinical studies suggest that these agents may reduce lesion growth, improve endothelial stability, and decrease vascular permeability. However, most current evidence remains experimental, and significant challenges remain in translating these findings into effective clinical therapies. Further large-scale clinical trials are required to determine the safety and efficacy of targeted pharmacological treatments for FCCM.